Certification and Labeling of Forest Products: Will It Lead to More Environmentally Benign Forestry in Maine? - Teisl, Mario; Peavey, Stephanie; O’Brien, Kelly (Maine Policy Review, 2001)
From a supply and demand point of view, the trend toward forest-products certification appears simple: some retail consumers may prefer to buy products from forests managed in an environmentally sound way while some forest owners may be willing to alter their management practices in order to sell to these consumers. However, as the authors indicate, the issue of communicating to consumers the degree of “environmental good” being purchased can be complicated and may be a factor affecting the long-term success of certification programs. The authors present the results of a recent survey that assessed the use of two types of consumer labels—eco-seals and eco-labels. They conclude that the current practice in the forest-products industry of using eco-seals alone to market the “environmental goodness” of products may not be as effective as other types of labels that provide consumers with detailed information about the product’s environmental attributes.
Keywords: Maine; forest products certification; forest products labeling